Teori Komunikasi Perspektif Indonesia: Gagasan dan Kemungkinan - Abdul Hair (UMSU, 2020)
This article discusses the possibility of initiating the Indonesian perspective of communication theory, an idea that was derived, while also drawing inspiration, from the Asian perspective of communication theory offered by Kincaid and Dissanayake in the 1980s. The question raised in this article is, is it still relevant to formulate a communication theory based on Indonesian culture, as globalization has increasingly blurred the boundaries between